Design of a new type of piezoelectric linear motor base on non-resonant vibration - Pei-hong Chen; Yin Wang; Wei-qing Huang (Joint Conference of the 2009 Symposium on Piezoelectricity, Acosutic Waves, and Device Applications and 2009 China Symposium on Frequency Control Technology, 2009)
Summary form only given. Based on the piezoelectric ceramics stack had a big amplitude of displacement during low frequency, a new type of piezoelectric linear motor based on non-resonant vibration was proposed. The working principle of the motor was presented, the structure was designed by finite element software, and a prototype was made. The mechanical property of the motor was preferable during low frequency, its operating frequency was adjustable and working state was stable under the interference of external factors. The result of experiment shows that the motor could work in the frequency between 300Hz and 7KHz, the speed of the motor is proportional to the operating frequency. The maximum velocity is 5mm/s and the maximum thrust force of the motor is 4.8N.